Make a Match Techniques in Cooperative Learning: Innovations to Improve Student Learning Outcomes, Student Learning Activities and Teacher Performance - Viyayanti; Dwikoranto (Indonesia Approach Education, 2021)
The purpose of this study is to describe improving student learning outcomes, describe student activities, describe teacher performance after applying the make a match technique in cooperative learning. This learning improvement is carried out by classroom action research, with steps of planning, implementing, observing, revising. The research subjects were 34 students in the chemistry class of Vocational School 1 Cerme Gresik. Data were analyzed descriptively quantitatively. The results of the class average score before the action was 70. Students who scored above the Minimum Completeness Criteria (MCC) 76 were 16 students (47%) with the highest score of 92 and students who scored below the MCC were 18 students (53%) with the lowest score of 40. After taking action in cycle 1 the average grade of 79. Students who scored above or equal to the MCC were 26 students (76%) with the highest score of 100 and students who scored below the MCC were 8 students (24%) with the lowest score of 52. Cycle 2 the average grade of 84. Students who scored above the MCC were 31 students (91%) with the highest score of 100, while students who scored below the MCC as many as 3 students (9%) with the lowest score of 64. The students' attention, activity, and enthusiasm for learning increased. Teacher performance in learning has increased.